Serosurvey of Coxiella burnetii (Q fever) in dromedary camels (Camelus dromedarius) in Laikipia County, Kenya - Browne, A.S.; Fèvre, Eric M.; Kinnaird, M.; Muloi, Dishon M.; Wang, C.A.; Larsen, P.S.; O'Brien, T.; Deem, S.L. (Wiley, 2017)
Dromedary camels (Camelus dromedarius) are an important protein source for people in semi-arid and arid regions of Africa. In Kenya, camel populations have grown dramatically in the past few decades resulting in the potential for increased disease transmission between humans and camels. An estimated four million Kenyans drink unpasteurized camel milk, which poses a disease risk. We evaluated the seroprevalence of a significant zoonotic pathogen, Coxiella burnetii (Q fever), among 334 camels from nine herds in Laikipia County, Kenya. Serum testing revealed 18.6% positive seroprevalence of Coxiella burnetii (n = 344). Increasing camel age was positively associated with C. burnetii seroprevalence (OR = 5.36). Our study confirmed that camels living in Laikipia County, Kenya, have been exposed to the zoonotic pathogen, C. burnetii. Further research to evaluate the role of camels in disease transmission to other livestock, wildlife and humans in Kenya should be conducted.